Britain, détente, and changing East-West relations - White, Brian, 1947- (Routledge, 1992)
Argues that Britain's contribution to East-West detente has been consistently undervalued. Re-evaluates Britain's role in the post-war world and provides a valuable case study in foreign policy formulation and implementation.